2022
DOI: 10.3389/fpubh.2022.967440
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge and attitude of healthcare professionals regarding the use of telemedicine: A cross-sectional study from rural areas of Sindh, Pakistan

Abstract: BackgroundTelemedicine has proved its significance in the healthcare system, especially during the coronavirus disease 2019 (COVID-19) pandemic as it assists in the provision of early and effective healthcare to those in distant areas. This study aimed to assess the knowledge and attitude of healthcare professionals toward the use of telemedicine in the rural areas of Sindh, Pakistan.Materials and methodsThe cross-sectional study was conducted with 212 healthcare professionals including physicians, consultants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…Regarding practice of HITs, a 2022 study among health professionals from rural areas of Sindh in Pakistan found that 52.5% practiced telemedicine which is a similar finding to the current study [ 35 ]. The study from India found that 44% of the health professionals practice well which is lower than the current study's finding of 56% [ 28 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Regarding practice of HITs, a 2022 study among health professionals from rural areas of Sindh in Pakistan found that 52.5% practiced telemedicine which is a similar finding to the current study [ 35 ]. The study from India found that 44% of the health professionals practice well which is lower than the current study's finding of 56% [ 28 ].…”
Section: Discussionsupporting
confidence: 86%
“…These disparities might be attributed to the varying levels of digitalization in the workplaces of healthcare professionals [ 36 ]. The study from Sindh, Pakistan, found that taking training positively influences practice levels of health professionals [ 35 ]. However, in the current study, it was found that taking training was not related to practice habits of health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The survey findings highlight the importance of enhancing both internet and information technology infrastructures and the development of training programs for the medical staff. These steps are vital to ensure the safe and effective operation of teleophthalmology in the future, aligning with previous research [20,31,32].…”
Section: Discussionmentioning
confidence: 55%
“…Taking into account the above findings and analyzing other surveys, Pakistan, especially the rural areas of Sindh, still lagging to use the telemedicine to the full potential 12 . Certain factors are there, that need to be properly addressed and be worked upon to resolve the issues that prevent the effective use of telemedicine facilities in underserved areas of Sindh 10 , 11 .…”
Section: Introductionmentioning
confidence: 85%